Collaborative governance in action: driving ecological sustainability in the Yangtze River basin - Xia, Yue; Tian, Ze; Ding, Chenhui (Frontiers in Environmental Science, 2024)
Implementing a collaborative governance framework across administrative boundaries is crucial for preserving the Basin’s ecological integrity and mitigating institutional fragmentation. Based on 19 cases of inter-provincial collaborative governance of ecological environment in the Yangtze River Basin of China, this study uses the fuzzy set qualitative comparative analysis method to explore the influencing factors and complex causal mechanism of the effect of inter-provincial collaborative governance. The results show that technology empowers relationship driving, institutions reinforce interactive driving, and internal and external interaction driving modes promote collaborative governance. Perceived factors are essential in motivating provinces to participate in collaborative governance. External factors play a hygienic role in collaborative governance, and internal factors play a motivated role. The roles of the two types of factors are separate but complementary. In view of this, government should attention to regional environmental concerns, ensuring consistent alignment of internal and external factors and fostering synergies to improve governance effectiveness.